Did SARS-CoV-2 Also Contaminate Swiss Mass Media? A Retrospective Analysis of French-Speaking News Articles During the First Pandemic Wave - Carole Kebbi-Beghdadi; Arnav Sandu; Beatrice Schaad; Gilbert Greub (COVID)
Given the critical role of media in times of crisis, particularly for relaying scientific knowledge and political decisions, we evaluated to what extent the first COVID-19 pandemic wave affected the treatment by traditional media of important societal topics. We searched a database of 650 French-speaking Swiss media outlets using specific keywords and reported the number of publications per month containing these items, associated or not with SARS-CoV-2. The number of publications related to viruses increased 12-fold during the first semester 2020, while the media coverage of topics about bacteria, parasites, and fungi remained stable. During the first pandemic wave, media generated a larger number of publications treating of political and medical subjects than before the pandemic, whereas the coverage of other topics was unchanged. All topics were viewed through the prism of the pandemic, up to 82% of the publications being associated with COVID-19. The media largely covered all medical aspects related to SARS-CoV-2 infection and offered scientists multiple opportunities to communicate with the public. However, their influence was strongly challenged by the capacity of social networks to disseminate rumors and misinformation. We also assessed the articles published in traditional media during the five subsequent epidemic waves, showing that the largest media peaks occurred during the first infection wave studied extensively in the present work, and during the huge fifth infection wave due to Omicron variant BA1. Undoubtedly, the COVID-19 pandemic highlighted how important it is for science communication to harness the tremendous power of social media.